Corticobasal syndrome as a focal variant of Alzheimer’s disease: Síndrome corticobasal como variante de la enfermedad de Alzheimer - Mariani, Francesca; Damian, Andrés; Duarte, Pablo; Pino, Stephanie; Dansilio, Sergio; Ferrando, Rodolfo (Journal of Applied Cognitive Neuroscience, 2022)
We present A 60-year-old woman with a 2-year history of progressive anterograde memory deficit, with a A 18F-FDG PET/CT and 11C-PIB PET/CT studies performed. In the follow-up she presented a typical corticobasal syndrome with extrapyramidal signs and left superior limb dystonia. These clinical and imaging features are consistent with a focal presentation of AD.